Yangyinqingfei decoction attenuates PM2.5-induced lung injury by enhancing arachidonic acid metabolism - Tang, Chunlan; Tang, Yuqing; Wang, Qinwen; Chu, Donghui; Zhou, Jinyue; Zhou, Yuping (Frontiers in Pharmacology, 2022)
Yangyinqingfei Decoction (YYQFD), a traditional Chinese prescription, is well known in the treatment of diphtheria and lung-related diseases in clinic. However, whether it can be used to block the lung injury caused by air pollutant remains unclear. In the present study, the effect of YYQFD was addressed using a PM2.5-induced lung injury mice model. It was shown that YYQFD significantly improved pulmonary functions of mice exposed to PM2.5, the levels of IL-6, TNF-α and MDA were decreased while SOD levels were increased in serum and bronchoalveolar fluid. The potential mechanism of YYQFD was then delved using metabolomics and proteomic techniques. The protein-metabolite joint analysis showed that YYQFD regulated the biosynthesis of unsaturated fatty acids, linoleic acid and arachidonic acid metabolism, causing a significant decrement of pro-inflammatory mediator arachidonic acid with its downstream metabolites like 20-HETE, prostaglandin E2, accompanied by the up-regulation of PTGES2, GPX2 and CBR3 in lung tissue. These data were used to construct a regulatory metabolic network map in terms of the therapeutic role of YYQFD in PM2.5-induced lung injury, thereby provided a novel insight into potential application in the respiratory diseases caused by air pollutants.